מהי הנוסחה של x ^ 3 - y ^ 3 - z ^ 3 -3xyz ???

מהי הנוסחה של x ^ 3 - y ^ 3 - z ^ 3 -3xyz ???
Anonim

תשובה:

(x-y-z) (x ^ 2 + xy + y ^ 2 + xz-yz + z ^ 2) #

הסבר:

הוכחה:

שים לב ש # x = y + z # הוא פתרון של

# x ^ 3-y ^ 3-z ^ 3-3xyz = 0 #

חיבור # x = y + z # במשוואה לעיל:

# (y + z) ^ 3-y ^ 3-z ^ 3-3 (y + z) yz = y + 3 + 3y ^ 2z + 3yz ^ 2 + z ^ 3-y ^ 3-z ^ 3-3y ^ 2z-3yz ^ 2 = 0 #

כדי שנוכל לחלק # x ^ 3-y ^ 3-z ^ 3-3xyz # מחולק ב # x-y-z #

ואנחנו מקבלים

# x ^ 2 + xy + y ^ 2 + xz-yz + z ^ 2 #